The genus Terpios (Suberitidae) and new species in the “Lobiceps” complex. Pp. 381-393. In: Uriz, M.-J. & Rützler, K. (Eds), Recent Advances in Ecology and Systematics of Sponges. - Rützler, K.; Smith, K.P. (Scientia Marina,, 1993)
The genus Terpios, first described from the Atlantic Ocean (West Indies) almost 130 years ago, is redefined on the basis of structural studies of tylostyles and data on procaryotic symbionts. Its relation to similar genera in the family Suberitidae is reviewed by comparing new findings with traditionally used characters, such as body shape, skeleton arrangement, and spicule size. Two new species, T. manglaris and T. belindae, are described from shallow-water habitats in the Caribbean Sea. They resemble Suberites lobiceps Schmidt, a poorly known sponge from Florida that has not been found since its first description in 1870.
Proceedings of the 8th Workshop on Atlanto-Mediterranean Sponge Taxonomy